Contraction of axonal and dendritic fields in Sox5-deficient cone bipolar cells is accompanied by axonal sprouting and dendritic hyper-innervation of pedicles - Kulesh, Bridget; Reese, Benjamin E.; Keeley, Patrick W. (Frontiers in Neuroanatomy, 2022)
Multiple factors regulate the differentiation of neuronal morphology during development, including interactions with afferents, targets, and homotypic neighbors, as well as cell-intrinsic transcriptional regulation. Retinal bipolar cells provide an exemplary model system for studying the control of these processes, as there are 15 transcriptionally and morphologically distinct types, each extending their dendritic and axonal arbors in respective strata within the synaptic layers of the retina. Here we have examined the role of the transcription factor Sox5 in the control of the morphological differentiation of one type of cone bipolar cell (CBC), the Type 7 cell. We confirm selective expression of SOX5 in this single bipolar cell type, emerging at the close of the first post-natal week, prior to morphological differentiation. Conditional knockout mice were generated by crossing a bipolar cell-specific cre-expressing line with mice carrying floxed Sox5 alleles, as well as the Gustducin-gfp reporter which labels Type 7 CBCs. Loss of SOX5 was confirmed in the bipolar cell stratum, in GFP+ Type 7 cells. Such SOX5-deficient Type 7 cells differentiate axonal and dendritic arbors that are each reduced in areal extent. The axonal arbors exhibit sprouting in the inner plexiform layer (IPL), thereby extending their overall radial extent, while the dendritic arbors connect with fewer cone pedicles in the outer plexiform layer, showing an increase in the average number of dendritic contacts at each pedicle. SOX5-deficient Type 7 CBCs should therefore exhibit smaller receptive fields derived from fewer if now hyper-innervated pedicles, transmitting their signals across a broader depth through the IPL.